The nature and motivation of Human Capital Reporting (HCR): a preliminary study / Shukriah Saad and Mohamat Sabri Hassan - Saad, Shukriah; Hassan, Mohamat Sabri (Accounting Research Institute & Faculty of Accountancy, 2013)
The purpose of this paper is to explore the external disclosure of human capital (HC). This study aims to examine the nature of human capital reporting of public listed companies in Malaysia, investigate the motivational motive towards the extent of human capital reporting from preparer’s point of view and identify the problems that might be faced in reporting human capital information. This study is based on a cross-sectional examination of disclosures on HCR by 20 public listed companies in Malaysia. The information about human capital presented in annual reports is grouped into five themes defined in the literature. A content analysis of these 20 annual reports is conducted to measure the nature and level of HCR. Besides the number of sentence count, narrative text unit adopted from Beattie et al. (2004) is also applied as unit of analysis. A questionnaire survey for HR managers of the Malaysian listed companies is conducted to find out the respondents’ motivation to disclose information in respect of reported items of HCR. Responses are compared with the results obtained from the measured HCR through content analysis. The findings demonstrate the most reported items of human capital, a comprehensive and descriptive profile of narrative disclosures of human capital items as well as the rank of motives for disclosures. Trading and the services industry have the highest score for the number of sentence count and the narrative text unit. The most reported items by sentence and narrative text unit are the working environment and employee’s involvement in the community.